Virtual panel discussion with VK7 and DM54 candidates organized by UiTM Perak Branch administration office/ Al-Amin Abdul Razi - Abdul Razi, Al-Amin (Universiti Teknologi MARA, Perak, 2021)
15 September 2021- Seri Iskandar Campus Administration Off ice has organized a briefing session withVK7 and DM54 virtually using Google Meet application beginning at 8.30 a.m and ended at 12.00 p.m.Promotion refers to advancing an employee's rank or position in a hierarchical structure. The purpose of of the virtual discussion was focusing on grooming potential candidate to be futureleaders at higher grade DM54 and VK7. This is in line with the campuses quality objective to increasenumber of Professor and Associate Professor in the organisation.